MALE IN VELIKE TEŽAVE „PRAVILNE“ SLOVENŠČINE - Andrej Rozman Roza (Philological Studies, 2019)
As the Slovenian language is one of the rare common identity shared by all Slovenian nationals, Slovenians are unduly sensitive to the influence of foreign tongues on their own language. This is the reason behind the great divide between the actual Slovenian language and its idealized image. By advocating the use of “correct” Slovenian in films – where it does not belong due to the nature of the medium – the Slovenian linguistic establishment damaged the Slovenians’ relationship to their own cinema.